Degradasi Zat Warna Methanil Yellow Menggunakan Metoda Fotosonolisis dengan Bantuan Katalis ZnO - Reska Putri; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2022)
Research that has been carried out on the photosonolysis degradation of methanyl yellow using a ZnO catalyst aims to determine the effect of radiation time on the degradation of methanyl yellow. The degradation time is about 30 to 150 minutes using a ZnO catalyst. The measurement results of the Uv- Vis spectrophotometer were obtained at a wavelength of 437nm. In the variation of the degradation time, the highest result was obtained at 60 minutes which was 76,11 %. This study showed that the hydroxyl radical (∙OH) was the main control in degrading methanil yellow